Retraction of Published Article Due to the Author’s Proposal - UGM, Jurnal Ilmu Kehutanan (Universitas Gadjah Mada, 2025)
Article: Jurnal Ilmu Kehutanan, 19(1) 2025, pp. 92-101 (10.22146/jik.v19i1.19038)Title: Chemical compound Analysis of Syzygium myrtifolium Essential Oil and Molecular Docking Analysis on Phenylalanine Hydroxylase EnzymeAuthor: Zikri HamidiAccording to the author’s proposal, the editorial of the Jurnal Ilmu Kehutanan withdraws the paper. 26 June 2025